Overlapping and distinct phenotypic profiles in Alzheimer’s disease and late onset epilepsy: a biologically-based approach - Liu, Anli A.; Barr, William B. (Frontiers in Neurology, 2024)
Due to shared hippocampal dysfunction, patients with Alzheimer’s dementia and late-onset epilepsy (LOE) report memory decline. Multiple studies have described the epidemiological, pathological, neurophysiological, and behavioral overlap between Alzheimer’s Disease and LOE, implying a bi-directional relationship. We describe the neurobiological decline occurring at different spatial in AD and LOE patients, which may explain why their phenotypes overlap and differ. We provide suggestions for clinical recognition of dual presentation and novel approaches for behavioral testing that reflect an “inside-out,” or biologically-based approach to testing memory. New memory and language assessments could detect—and treat—memory impairment in AD and LOE at an earlier, actionable stage.